Residual Stress, Thermomechanics & Infrared Imaging and Inverse Problems, Volume 6 : Proceedings of the 2019 Annual Conference on Experimental and Applied Mechanics /: Proceedings of the 2019 Annual Conference on Experimental and Applied Mechanics. (2020) - Unknown
No abstract available